Pengembangan Destinasi Wisata Halal (Halal Tourism) dalam Meningkatkan Kesejahteraan Masyarakat - Muh. Salim Rahmatulloh (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Da'wah has a goal so that people have a better life, both materially and immaterially. This study aims to find out how the development of Halal Tourism Destinations can build new changes, namely increasing people's welfare. The research method uses a descriptive qualitative approach. The results showed that; 1). Nature management that is beneficial to the community 2). Increase the job field is getting wider 3). Unemployment is decreasing 4). The environmental potential is increasingly being managed 5). Able to reduce poverty and grow the level of community welfare is getting better. This research has a practical, theoretical impact that the concept of halal tourism development has the substance value of da'wah and can improve the community's welfare as part of da'wah bil hal.